Review of International Law Against Diplomatic Immunity Consulate General Who Committed A Violation of Law In The Recipient Country - Iffan, Ahmad (Universitas Muhammadiyah Metro, 2024)
Diplomatic immunity granted to an official such as a consular official who is granted privileges and immunities regulated by the 1963 Vienna Convention as the basis of international law where the receiving State is obliged to guarantee and protect the privileges and immunities of consular officials. The principle of reciprocity which is one of the bases for the granting of immunity between representatives of the two countries in each recipient country makes the legal system of diplomatic representation more concrete and good. Based on the mechanism of international law, the US has committed a violation of international law, namely not protecting or complying with the provisions regarding diplomatic representatives who have immunity rights. Even if an official commits no crime or violation, the person who has the authority should ask permission from the country of origin of the diplomatic representative, this is useful for maintaining good relations between countries and between their citizens. Resolving violations by respecting representatives can conclude that the country has good faith in maintaining relations. The highest authority lies with the sending country which has full sovereignty over its representatives in each country.